Chemical Composition And Bioactive Properties Of Three Walnuts (Juglans Regia L.) Cultivars Planted In Syria (Damascus University Journal of agriculture sciences, 2021)
This study was done at the department of food Science, faculty of agriculture during 2012. The aim of this study was to determine the chemical composition and bioactive properties of  three  walnuts cultivars (Belhsin 1, Belhsin 2, and Belhsin 3) which planted in Syria and classified morphologically and genetically by the Agricultural Research Center  . Results revealed that the total oil content  ranged  from 68.99 to 71.96% which correspond an energy value of approximately 719.04 kcal/100g of fruit ; water content ranged from 2.7 to 3.3%  ; ash ranged from  1.11 to 1.28% and protein ranged from 18.05 to 22.2% . Linoleic acid was the major fatty acid reaching the maximum value of  60.1% (Belhsine 2) followed by oleic, linolenic and palmitic acid. The total phenolic compounds ranged from 991.7 to 1570.05 mg/100g Caffic acid Eq., and the antioxidant activity ranged from 76.12 to 78.99 % measured as colorimetric DPPH method. Belhsine 3 showed higher percentage of total phenolics and antioxidant than Belhsine 1 and 2.
Keywords: Chemical composition; Bioactive properties; Walnuts